The Influence of Content Marketing on Customer Loyalty: Case Study of Spotify - Luthfiyyah, Adinda Rizki; Rufaidah, Popy (Economics and Business Journal (ECBIS), 2025)
This study aims to examine the influence of marketing content dimensions—namely product content, service content, advertising content, and brand culture—on customer loyalty toward Spotify, which encompasses cognitive, affective, conative, and action loyalty. A quantitative research approach was employed, utilizing Partial Least Squares Structural Equation Modeling (PLS-SEM) and bootstrapping techniques, with data collected from 145 Spotify users through an online survey. The findings reveal that not all marketing content dimensions exert a significant impact on every facet of customer loyalty. Service content and brand culture emerged as the most influential factors in driving action and conative loyalty, whereas product content predominantly affected cognitive and affective loyalty. This research underscores the critical need for tailored content strategies to effectively foster specific types of customer loyalty within the digital streaming service context. The managerial implications of these results provide a foundation for developing more effective, user experience-oriented marketing content strategies.